PENGATURAN OPSEN PAJAK GUNA MENINGKATKAN PENDAPATAN ASLI DAERAH DI KABUPATEN SUKOHARJO - Pranata, David Arya (Res Publica: Jurnal Hukum Kebijakan Publik, 2025)
This article aims to determine the tax opsen arrangement in Sukoharjo Regency. In addition, it is also to determine the impact of the tax opsen arrangement. This research uses a descriptive normative type, using secondary legal sources and primary, secondary, and tertiary legal materials. The article conducted in this writing is research on the regulation of the law by examining the laws and regulations on Tax Opsen. Tax Opsen arrangement has various impacts, including accelerating the receipt of Regional Original Revenue (PAD) in the Regency / City, Increasing Regional Independence, Increasing Revenue in the Regency / City, Increasing the Taxpayer's Burden, and Decreasing Revenue in the Province. The regulation of tax opsen in Sukoharjo Regency is contained in Sukoharjo Regency Regional Regulation Number 10 of 2023 concerning Regional Taxes and Levies, especially in Article 1, Article 2, Article 3, Article 49 to Article 53, Article 54 to Article 58, and Article 136. The Tax Opsen arrangement is actually a transfer of provincial tax revenue sharing that can increase regional independence without increasing the burden on taxpayers because it is directly recorded as Regional Original Revenue (PAD) and also supports better planning, budgeting, and realization of the APBD.